Is Leaving God to Make the Choice an Answer to a Charge of Murder by Reckless Indifference to Human Life or Manslaughter? A Case Study of Queensland Criminal Law - Andrew Hemming (Australian Journal of Law & Religion)
The criminal law punishes persons who commit a guilty act with the requisite guilty mind. This article considers the criminal responsibility of parents and other persons who claim not to have possessed a guilty mind but instead left the choice to God as to whether a child survived the withdrawal of medication. The critical question is whether a jury can infer actual knowledge that death would probably result when a person consciously avoids considering the ramifications of withholding lifesaving medicine, such as insulin to a child with diabetes, and instead hands moral responsibility to God. This article explores whether murder under the circumstance of reckless indifference to human life, defined as an act committed with an awareness that death will probably arise from that act or omission, encompasses a defendant whose awareness is affected by a religious belief that his or her religious faith required God to make the decision of life or death. To avoid the need for the jury to infer actual knowledge from the objective circumstances of the case, the argument is made for an objective test for recklessness based on the natural and probable consequences test. The Crown’s options in framing the charges to be laid and the reasons why a particular choice may be made are considered, particularly in relation to manslaughter. In addition, this article examines the reach of criminal responsibility where the parents of the child are joined in prayer in their own home by members of the religious group to which the parents belong.